PENERAPAN SANKSI PIDANA PENJARA DAN DENDA TERHADAP PEGAWAI NEGERI SIPIL YANG MELAKUKAN TINDAK PIDANA KORUPSI PUNGUTAN LIAR (STUDI DI PENGADILAN TINDAK PIDANA KORUPSI PONTIANAK) - HARJANTO, SH A.21212022, Jurnal Mahasiswa S2 Hukum UNTAN (Jurnal NESTOR Magister Hukum, 2016)
ABSTRACTThis thesis is studies of the issue of sanction of imprisonment and fines against civil servants who undergo corruption extortion (Study In Pontianak Corruption Court). From the results of research using normative legal research we concluded that: 1. The application of criminal sanctions can dimaknakan as deeds, actions or judgments in criminal dropped against defendants who were accused of general or specific in criminal justice proceedings. Theoretically, juridical and empirical, the judge in applying criminal sanctions must be referring to the philosophical core of truth and justice, cored juridical norms of legal certainty and legal expediency, as well as sociological value taking into account cultural values that live and thrive in the community. When examined Pontianak District Court No. 14 / Pid.Sus / TP.Korupsi / 2013 / PN.PTK, then tetlihat that the judges only consider the juridical aspect alone. While the philosophical and sociological aspects are not taken into consideration at all. So that the imposition of sanctions of imprisonment for 1 (one) year and 6 (six) months and a fine of Rp. 50 000 000, - (fifty million dollars) with the provision that if the fine is not paid to be replaced by imprisonment for 1 (one) month is considered not reflect the value of substantive legal justice. 2. To give the value of truth, fairness, certainty, and legal expediency better into the future, the application of criminal sanctions against corruption by judges should be guided by the purpose of the criminal justice and sentencing guidelines as set out new Criminal Code or after the adoption of the Draft Bill Draft Definitive 13 to the Criminal Code. Selanjunya recommended, harmony with the provisions of Article 211 of the Criminal Code First Book Draft Bill 13, which determines the